Effects of calcium oxide on nitrogen oxide precursor formation during sludge protein pyrolysis. (15th December 2019) - Guo, Shuai; Liu, Tiecheng; Hui, Jicheng; Che, Deyong; Li, Xingcan; Sun, Baizhong; Li, Shaohua
Abstract: The addition of CaO has been used to reduce the harmful NO x precursors (NH3 and HCN) generated by the pyrolysis of municipal sewage sludge. However, the underlying reduction mechanism remains unclear. To address this issue, we systematically investigated the effects of temperature and CaO addition on the generation of NH3 and HCN during the pyrolysis of sludge protein and a model protein. With increasing temperature from 300 to 900 °C, the inhibitory effect of CaO on NH3 emission was observed to fluctuate, maximizing at 400 °C. The inhibition was attributed to the reaction of CaO with nitrogen in the produced char to form CaC x N y, resulting in enhanced fixation of the char pyridines and nitriles. The nitriles exhibited high thermal stability and inertness to CaO. The increased nitrile content at high temperatures was attributed to the formation of the species from amines and N-containing heterocycles. The CaC x produced by the thermal decomposition of CaC x N y above 700 °C was found to increase P–N fixation and decrease NH3 formation. The observed poor inhibitory effect of CaO on NO x precursor formation at 650 °C was attributed to the production of NH3 via HCN hydrolysis. Because HCN directly reacted with CaO, the inhibition of HCN formation was highest at 650–900 °C, preventing the conversion of char nitriles into HCN. Highlights: CaO inhibits NH3 and HCN formation during sludge protein pyrolysis. Within 300–900 °C, inhibitory effect on NH3 fluctuates, maximizing at 400 °C. Inhibition on HCN formation reaches highest at 650–900 °C. Inhibition enabled by reaction of CaO with N in char to form CaC x N y .